Electro-Optical Performance of Surface-Emitting Micromirror Superluminescent Diodes - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Niebling, Tobias; Witzigmann, Bernd (Physica Status Solidi-Rapid Research Letters, 2019)
Output power characteristics and efficiency of novel surface-emitting superluminescent diodes are presented. Tilted micromirrors terminate an in-plane waveguide, and laterally gain-guided modes are deflected perpendicularly to the anti-reflection-coated chip surface. The epitaxial structures are grown by a metal-organic vapor-phase epitaxy with several InGaAs/GaAs quantum wells emitting at a peak wavelength of 950 nm, and the chip technology involves only wafer-scale processes. The spectral full width at half maximum of the amplified spontaneous emission is larger than 10 nm. In a pulsed operation, a room temperature output power that exceeds 250 mW with a wall-plug efficiency higher than 15% is achieved.
CRIS-Team Scopus Importer:2021-06-11
Keywords: micromirrors; superluminescent diodes; surface emission; thin-film technology